환자안전 관리와 전망 - 염호기 (Taehan Ŭisa Hyŏphoe chi, 2013)
Patient safety has been one of the hottest issues of healthcare quality in Korea since two years ago. Patient safety is defined as avoiding risk and minimizing harm. It is a new concept to transform all services to add value in healthcare, not only to address the effectiveness of treatment but also errors, inefficiency, preventable complications, and unnecessary treatment. To reduce risk and improve the effectiveness of health care quality,health care organizations should operate a patient safety reporting system and learning program. For the purpose of promoting improvements in health care quality and patient safety of hospitals, patient safety standards in an accreditation system were implemented by the Korea Institute for Healthcare Accreditation. Lessons from an error reporting system provide important solutions to management of sentinel events in health care organizations. The current status of policies, strategies, and reporting systems for patient safety were reviewed and in addition, a few suggestions have been added to advance patient safety in Korea. KCI Citation Count: 0